URGENSI KARTU DANA OTONOMI KHUSUS BAGI ORANG ASLI PAPUA (TINJAUAN DESENTRALISASI ASIMETRIS DI INDONESIA) - Ni Luh Putu Geney Sri Kusuma Dewi (Jurnal Aktual Justice, 2021)
Decentralization is one of the political choices in order to ensure the implementation of government affairs in the regions. History has noted that Indonesia has attempted (still) an ideal formula in the administration of local government, starting from the implementation of symmetrical or asymmetrical decentralization. This is not an easy matter considering the diversity that exists in each region, so a special method is needed to be able to fulfill the wishes of each region proportionally. The decentralization that Indonesia needs does not seem to be just ordinary decentralization, empirically Indonesia has actually implemented what is called asymmetric decentralization or decentralization that is not the same/not uniform for each region. The Papua region is an example of the implementation of asymmetric decentralization, but the problem is that the special labeling of the region reflects an asymmetrical framework, namely a serious effort designed to accommodate regional needs by considering all aspects based on regional needs. This means that in granting asymmetric decentralization to a region, it does not mean that it only fulfills sporadic needs based on bad experiences, namely the failure to carry out symmetrical decentralization as in other regions. Therefore, the author considers it important to analyze more deeply the special labeling for Papua has been given in accordance with the asymmetric decentralization framework or only meets sporadic demands to anticipate the issue of disintegration.